Oat—an alternative crop under waterlogging stress? - Pitann, Britta; Mühling, Karl H. (Frontiers in Plant Science, 2024)
Introduction Waterlogging is one vast environmental constraint that limits crop growth and yield worldwide. Most major crop species are very sensitive to waterlogging, leading to enormous yield losses every year. Much is already known about wheat, barley or maize; however, hardly any data exist on oat and its tolerance against waterlogging. Thus, this study aimed to investigate if oats can be an adequate alternative in crop rotation under conditions of temporal submergence and if cultivar differences exist. Furthermore, this study was to test (1) whether yield was differently affected when stress is applied at different developmental stages (BBCH 31 and 51), and (2) nutrient imbalances are the reason for growth restrictions. Methods In a large-scale container experiment, three different oat varieties were cultivated and exposed to 14 consecutive days of waterlogging stress at two developmental stages. Results Even though vegetative growth was impaired after early waterlogging and which persists till maturity, mainly due to transient nutrient deficiencies, growth performance after late waterlogging and grain yield of all three oat varieties at maturity was not affected. A high tolerance was also confirmed after late waterlogging in the beginning generative stage: grain yield was even increased. Discussion Overall, all oat varieties performed well under both stress treatments, even though transient nutrient imbalances occurred, but which were ineffective on grain yield. Based on these results, we conclude that oats, independently of the cultivar, should be considered a good alternative in crop production, especially when waterlogging is to be expected during the cultivation phase.